Assessment of Medication Complexity and Adherence in Geriatric Patients - Andhi, Nikhilesh; Pravalika, J; Teja, M Surya; Prasanna, V Thulasi; Suma, CH Sai (Indian Journal of Pharmacy Practice)
Objectives: The main objective of the study was to assess the medication complexity and adherence in geriatric patients. Materials and Methods: On the geriatrics department of a tertiary care hospital, prospective observational research was done. A total of 280 patients were analyzed with the data collection form by interviewing the patients about the demographic questionnaire. The complexity of the regimen was assessed using the Medication Regimen complexity Index (MRCI) tool. The data were collected from the inpatient and out-patient department for a period of six months. The data are subjected to statistical tests like the Chi-square test using SPSS software. Results: There were 280 geriatric patients in all, with male patients outnumbering female patients 176. The majority of geriatric patients (79.27%) were in the 60–75 year age range. Cardiovascular illnesses were reported to be the most prevalent ailment in 94 (33.57%) patients. Level of complexity was higher for majority of prescriptions 196 (70%) with Tablets/ Capsules 280 (100%) and ‘Once in a day’ dosing frequency 276 (98.57%), additional/ administration instruction was prescribed for only few prescriptions 206 (73.57%) and if the patient was prescribed with more than 5 drugsfor about 218 patients (77.86%). The bulk of the population, or 156 people, exhibit moderate adherence (55.71%), followed by good adherence (76 people, 27.14%), and lastly low adherence (48 people, 17.15%). The complexity of the regimen was identified as the primary cause in 56 (27.45%) patients, and a comparison of the MRCI and MMAS revealed that patients on less complex regimens demonstrated moderate (40.148% patients) or good (34.124% patients) adherence. Conclusion: Geriatrics, which affects predominantly senior men (60 to 75 years old). The current study revealed a correlation between high MRCI scores for dosage form, dosing frequency, and additional/administration instructions and the current medical condition, the number of co-morbidities present, and the number of drugs prescribed; as a result, the MRCI serves as a better tool to assess the complexity of regimens. MMAS helps to assess the adherence level in geriatrics, which can be improved by removing barriers. With this, we can raise the geriatrics’ quality of life in terms of their health.
Keywords: Geriatrics; Medication regimen complexity index (MRCI); Dosage form; Dosing frequency; Additional/administration instructions; Moriskys medication adherence scale (MMAS)